Why cooperation fails? An analysis of mechanisms and models in cross-border governance: a systematic literature review - Cai, Jingwen; Yin, Yifen; Peng, Yanchong; Xie, Yingchong; Hu, Haoqian; Jin, Hui; Wang, Chunning (Frontiers in Political Science, 2025)
While cross-border cooperation is a vital governance model for transnational challenges, many initiatives ultimately fail. Existing research exhibits a “cooperation bias,” focusing more on the conditions for success than on the systemic causes of failure, thus leaving a significant research gap. To address this gap, this study follows the PRISMA guidelines and employs a systematic literature review to conduct an in-depth thematic analysis of 138 academic articles specifically documenting cases of cross-border governance failure. The findings reveal that governance failures can be classified into an integrative typology comprising three core dimensions: (1) institutional design failure (e.g., hollowed-out implementation and monitoring, fragmentation of authority and responsibility); (2) political dynamics failure (e.g., primacy of national interests and sovereignty, asymmetric power relations); and (3) socioeconomic contextual failure (e.g., resource and capacity gaps, normative and cultural conflicts, and scale mismatches between problem and its governance). This study’s primary contribution is the systematic construction of an analytical framework for cross-border governance failure. By engaging in a critical dialogue with mainstream governance theories, the research challenges their inherent “cooperation bias” and argues that a profound understanding of failure is essential for both theoretical advancement and the construction of more resilient governance models.